High current carbon nanotube cathode for miniature high power THz source application - Ang, Ricky Lay Kee (2008)
This RG 100/05 (SEP) is a supplement fund to support the A*STAR SERG grant 042 101 0080 entitled “High Current Carbon Nanotube (CNT) Cathode for Miniature High Power THz sources” (Jan 2005 –Jan 2008), where the PI is Asst Professor Ang Lay Kee, Ricky. For coherent radiation at THz frequency using Smith-Purcell based free electron laser (SP-FEL), a high current electron beam is required.